PENGARUH POLA ASUH ORANG TUA TERHADAP PERILAKU DISIPLIN ANAK USIA 5-6 TAHUN DI PAUD TERPADU CERIA - Salmah, Siti; Ali, Muhamad; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out the influence of parental care pattern on the discipline behavior of children aged 5-6 years in PAUD Integrated Cheers Kecamatan Sungai Kakap. The method used in this research is descriptive with quantitative approach of correlational cause and effect form. The number of samples used as many as 32 children, namely children aged 5-6 years. The location of the research was conducted in PAUD Integrated Cheers Kecamatan Sungai Kakap. Data collection techniques used closed questionnaires and documentation. Data validity using Moment Product Correlation techniques. Data reliability using Croncbach's Alpha technique. Data from the questionnaire were analyzed using descriptive quantitative analysis, simple linear regression analysis and t test. The results of this study indicate that the parenting pattern of children aged 5-6 years in PAUD Integrated Cheerful Kakap River District included into the category of interval class is with the percentage of 62.55%. Disciplinary Behavior of children aged 5-6 years in PAUD Integrated Cheerful Kakap River District included into the category of interval class with a percentage of 62.5%. The result of simple linear regression analysis showed that there is a positive influence between parenting parenting with discipline behavior of children aged 5-6 years in PAUD Integrated Cheers Kecamatan Sungai Kakap with regression coefficient value of 0.484. This is reinforced by t test which shows that the tcount is bigger than ttable (2,718> 1,697), which means Ho is rejected and Ha accepted. Thus parenting pattern has an influence on the behavior of children aged 5-6 years in PAUD Integrated Cheers Kecamatan Sungai Kakap.  Keywords: Parenting Pattern, Discipline Behavior.